GRAPHICAL USER INTERFACE AND GRAPHIC DESIGN AND LAYOUT OF ATUTOR LCMS - Iscioglu, Ersun; Bahrami, Sasan (Iated-Int Assoc Technology Education A& Development, 2012)
Developments in computer and internet technology affect people's lives closely. These developments also lead to the development and change of the teaching / learning environments. Even within lifelong learning, it is seen that use of technology in teaching environments is starting to become a necessity for ordinary. Today, both in face to face and distance education applications, Learning Management Systems (LMS) or Learning Content Management Systems (LCMS) have become indispensible in learning environments. The main purpose of this study is to examine the open source coded ATutor Learning Content Management System (LCMS) in the perspective of Human-Computer Interaction, in terms of Graphical User Interface and Graphic Design and Layout. The study was carried out in general survey model. In this study, items in the Graphical User Interface and Graphic Design and Layout control list (checklist), determined by Johnson (2008) were used [1]. Data analyzed from on the basis of descriptive analyses. The findings in the study are offered correspondingly with the accompanying research questions. According to the findings, discussions and suggestions are provided at the end of the study.
5th International Conference of Education, Research and Innovation (ICERI) -- NOV 19-21, 2012 -- Madrid, SPAIN
Keywords: Graphical User Interface (GUI); Graphics Design and Layout; Learning Content Management Systems (LCMS); Virtual Learning Environments (VLE); ATutor